Chitty Chitty Bang Bang [compact disc, unabridged] - Fleming, Ian, 1908-1964 (Blackstone Audio, Inc., 2013)
"Crackpot" is what everybody calls the Pott family. So when they go to buy a new car and come back with a wreck, nobody is surprised--except for the Potts themselves. First, the car has a name, and she tells them what it is! Then they find out that she can fly--and swim. Chitty Chitty Bang Bang is a car on a mission to stop a criminal gang in its tracks--and she's taking the Potts with her.